Pengembangan Bahan Ajar Audiovisual Animasi Berbasis Aplikasi Powtoon Pada Mata Pelajaran Bahasa Jerman Kelas XI - Suratratan, Ivonsina; Serpara, Henderika; Noya van Delzen, June Carmen (Universitas Pattimura, 2025)
This study aims to develop audiovisual animated teaching materials using the Powtoon application for German language instruction in grade XI. The development followed the 4-D model (Define, Design, Develop, Disseminate), but was limited to the Develop stage. Initial data were obtained through a needs analysis of teachers and students at SMA Negeri 7 Ambon, which revealed a lack of engaging and interactive teaching materials in German language learning. The product developed was an educational animation video created with Powtoon, covering the topics “Sich und andere vorstellen” and “Schulsachen.” Validation results from subject matter experts and media experts indicated that the developed materials are highly feasible for use as learning media. The strength of the product lies in the integration of visual elements, text, voice narration, as well as contextual and cultural aspects of German, aligned with the principles of the Merdeka Curriculum. This study is expected to provide an innovative alternative for German language learning that is more engaging, interactive, and suited to the characteristics of 21st-century students.